Formal versus Informal Advisees - Inside the Brain of the Advisors - Morgan, Kristen; Shipman, Ashley E.; Lamers, Rebecca J.; Remington, Katie L.; Wallin, Robyn S. (My University, 2013)
Advisors and advisees typically evolve relationships that blend personal and professional elements in various ways. The purpose of this study was to analyze advisors' perceptions of the overall advising process as well as the formal versus informal advising processes by deploying the Critical Incident Technique (Flanagan, 1954).
Color poster with text and graphs.
Keywords: Advising style; Perception; Critical Incident Technique; Posters